Risk factor assessment and methods of management of anaemia in chronic kidney disease (CKD) - Kanchana, W.P.L.; Jayaratne, H.P.R.S.; Muthukumarana, P.V.U.; Gunatilake, M.; Sheriff, M.H.R.; Herath, C.; Nazar, A.L.M. (My University, 2008)
To assess the causes, socio-demographic factors and the management of anemia in patients with CKD, admitted to the hemodialysis units of three hospitals. Design, setting and methods: A descriptive cross sectional study was conducted at the dialysis units of the National Hospital of Sri Lanka (NHSL), Sri Jayawardenepura and Western Infirmary Hospitals. Data were collected from medical records of patients (N=150). Ethical clearance was obtained from the Ethical Review Committees of the Faculty of Medicine, Colombo and NHSL. Results: Most of the patients were between 35 to 55 years and 72.6% were males. Our study represented most of the districts in Sri Lanka, the majority (55.3%) being from Colombo. Hypertension (27.3%) was identified as the leading cause in both males and females, while diabetes (21.3%) was the second commonest. 10.7% patients had both hypertension and diabetes. Other causes comprised of glomerulonephritis, polycystic kidney disease, obstructive kidney disease, SLE and Alport's syndrome. In 20% of patients the cause was not identified. 10% were found to have severe anemia and the main mode of treatment was blood transfusion. Later they were given recombinant erythropoietin (rEPO). 60% had moderate anemia of which 65.6% had received rEPO while 17.8% had not received any treatment. Conclusions: The commonest causes leading to CKD are hypertension and diabetes. Main treatment option of anemia was rEPO which was started mostly at hemoglobin levels less than 9g/dl, but according to DOQI guidelines it should be commenced when hemoglobin level is 11g/dl.